Intake and sources of dietary fibre and dietary fibre fractions in Finnish children - Salo Tuuli EI; Niinistö Sari; Korhonen Tuuli E; Pastell Helena; Reinivuo Heli; Takkinen Hanna-Mari; Ilonen Jorma; Toppari Jorma; Knip Mikael; Veijola Riitta; Virtanen Suvi M (Cambridge Univ Press, 2025)
The current definition of dietary fibre was adopted by the Codex Alimentarius Commission in 2009, but implementation requires updating food composition databases with values based on appropriate analysis methods. Previous data on population intakes of dietary fibre fractions are sparse. We studied the intake and sources of total dietary fibre (TDF) and dietary fibre fractions insoluble dietary fibre (IDF), dietary fibre soluble in water but insoluble in 76 % aqueous ethanol (SDFP) and dietary fibre soluble in water and soluble in 76 % aqueous ethanol (SDFS) in Finnish children based on new CODEX-compliant values of the Finnish National Food Composition Database Fineli. Our sample included 5193 children at increased genetic risk of type 1 diabetes from the Type 1 Diabetes Prediction and Prevention birth cohort, born between 1996 and 2004. We assessed the intake and sources based on 3-day food records collected at the ages of 6 months, 1, 3 and 6 years. Both absolute and energy-adjusted intakes of TDF were associated with age, sex and breast-feeding status of the child. Children of older parents, parents with a higher level of education, non-smoking mothers and children with no older siblings had higher energy-adjusted TDF intake. IDF was the major dietary fibre fraction in non-breastfed children, followed by SDFP and SDFS. Cereal products, fruits and berries, potatoes and vegetables were major food sources of dietary fibre. Breast milk was a major source of dietary fibre in 6-month-olds due to its human milk oligosaccharide content and resulted in high SDFS intakes in breastfed children.